Interactions, images and texts a reader in multimodality - Norris, Sigrid, 1961-; Maier, Carmen Daniela (Trends in Applied Linguistics TAL., 2014)
This Reader is a comprehensive introductory text for the study of multimodality and offers a wide range of approaches and data sets illuminating the value of multimodal investigations for education, sociology, anthropology, linguistics, psychology, and communication. With an extensive list of further readings, suggested assignments, and an alphabetic glossary, the book is a useful companion to students and researchers alike.